Pneumonia due to Chlamydia pecorum in a Koala (Phascolarctos cinereus). Issue 4 (November 2016) - Mackie, J.T.; Gillett, A.K.; Palmieri, C.; Feng, T.; Higgins, D.P.
Summary: Chlamydiosis is a common infectious disease of koalas ( Phascolarctos cinereus ), but Chlamydia spp. have not yet been demonstrated to cause pneumonia in these animals. A juvenile male koala died following an episode of respiratory disease. At necropsy examination, the lung tissue was consolidated. Microscopical lesions in the lung included pyogranulomatous bronchopneumonia, proliferation of bronchiolar and alveolar epithelium and interstitial fibrosis. Hyperplastic bronchiolar epithelial cells contained aggregates of small basophilic punctate organisms, which were confirmed as chlamydiae by transmission electron microscopy and immunohistochemistry. Real-time polymerase chain reaction identified these as Chlamydia pecorum . This report provides the best evidence to date of chlamydial infection causing pneumonia in a koala, and the first evidence that C. pecorum is capable of infecting the bronchiolar epithelium of the koala.